HUBUNGAN ANTARA PERHATIAN ORANGTUA DAN HASIL BELAJAR PADA PEMBELAJARAN TEMATIK INTEGRATIF SISWA KELAS IV SD NEGERI KEMBANGARUM 2 MRANGGEN DEMAK - A.Y Soegeng; Zuhrotun Nisa' (Universitas PGRI Semarang, 2014)
More less the studying result of students in 4th SD Negeri Kembangarum 2 Mranggen that influences some aspects, one of aspects is her parents?óÔé¼Ôäó not careless with them. Parents?óÔé¼Ôäó is constitute the?é?á first educator for children so that her parents?óÔé¼Ôäó has have responsibility to the studying result her children. The problem in this research contents is about Is there any correlation between of parents?óÔé¼Ôäó attention and the study result for thematic integrative learning in 4th SD Negeri Kembangarum 2 Mranggen Demak?. The hypothesis is that there is positive and significant correlation between of parents?óÔé¼Ôäó attention and the study result for thematic integrative learning in 4th SD Negeri Kembangarum 2 Mranggen Demak. The kind of this research is quantitative research. This research use correlation methode and submited the data use questionnaire and test. The colected data are analysed using product moment formula. The finding is that > on significancy level of 0,05. So the?é?á conclusion is there is positive and significant correlation between of parents?óÔé¼Ôäó attention and the study result for thematic integrative learning in 4th SD Negeri Kembangarum 2 Mranggen Demak.